Diagnosis and management of glucokinase monogenic diabetes in pregnancy: current perspectives - Rudland, Victoria L (Diabetes Metab Syndr Obes, 2019)
Glucokinase–maturity-onset diabetes of the young (GCK-MODY) is an autosomal dominant disorder caused by heterozygous inactivating GCK gene mutations. GCK-MODY is one the most common MODY subtypes, affecting 0.1% of the population and 0.4–1% of women with gestational diabetes mellitus. Glucokinase is predominantly expressed in pancreatic beta cells and catalyzes the phosphorylation of glucose to glucose-6-phosphate. The unique kinetics of glucokinase enable it to change the rate of glucose phosphorylation according to the glucose concentration, thereby regulating insulin secretion. Individuals with GCK-MODY have mildly elevated fasting blood glucose levels (5.5–8.0 mmol/L) and regulate glucose perturbations to a higher set-point, resulting in a relatively flat glucose profile on a 75 g oral glucose tolerance test. The hyperglycemia is usually subclinical and may only be detected on incidental glucose testing. It is important to correctly identify GCK-MODY as the clinical course and management differs substantially from other types of diabetes. Diabetes-related complications are relatively uncommon, so glucose-lowering treatment is not usually required. The exception is pregnancy, where fetal growth and therefore glucose-lowering treatment are predominantly determined by whether or not the fetus inherits the GCK mutation. The fetal genotype is not usually known but can be inferred from serial fetal ultrasound measurements. If there is evidence of accelerating fetal abdominal circumference on serial ultrasounds, the fetus is assumed to not have the GCK mutation and treatment of maternal hyperglycemia is indicated to reduce the risk of macrosomia, Caesarean section and neonatal hypoglycemia. If there is no evidence of accelerating fetal growth, the fetus is assumed to have inherited the GCK mutation and will have a similarly elevated glucose set-point as their mother, so maternal hyperglycemia is not treated. With recent advances in genetic technology, such as next-generation sequencing and noninvasive fetal genotyping, the detection and management of GCK-MODY in pregnancy should continue to improve.